ANALISIS FAKTOR KEBERHASILAN CAPAIAN KINERJA BADAN LINGKUNGAN HIDUP PROVINSI JAWA TENGAH - Dimas Anugrah Dwi Saputra; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research has a purpose to describe and to analyze both the performance result and the factors of success performance of Environmental Agency of Central Java using a qualitative method with descriptive type. The results showed that the performance of Environmental Agency of Central Java has done well. Nevertheless, there are some obstacles such as the limit of human resources and the change of Local Goverment Regulation. The success performance driven factors is seen from aspects there are personal factor, leadership factor, team factor, system factor, and constextual factor. The result of this research is the performance of Environmental Agency of Central Java has done well. The obstacles inside are the limit of human resources and the determining of Regulation number 23 in 2014. The success performance support factors are personal factor, leadership factor, team factor, and system factor. Based on the result, the author recommend to the Environmental Agency of Central Java to fix the performance of Environmental Agency of Cental Java to be better and optimum.